2022
DOI: 10.1007/s43546-022-00394-0
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality: a recipe for youth unemployment in Africa

Abstract: Youth unemployment is a problem in Africa such that young people face almost double the unemployment rate as adults. With the booming population on the rise, youth unemployment can turn into a major catastrophe in the continent if not addressed. This study presents empirical evidence on how income inequality accelerates the problem. The study uses panel data from 42 African countries spanning 29 years from 1991 to 2020. The dependent variable is youth unemployment, and the independent variable is income inequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The economic literature supports the finding suggesting a positive relationship between income inequality and the unemployment rate (Cysne, 2009;Sheng, 2011, Mwakalila, 2022. In addition, Castells-Quintana and Royuela (2012) have shown that income inequality affects economic growth, especially when there is persistent unemployment.…”
Section: Literature Reviewmentioning
confidence: 78%
“…The economic literature supports the finding suggesting a positive relationship between income inequality and the unemployment rate (Cysne, 2009;Sheng, 2011, Mwakalila, 2022. In addition, Castells-Quintana and Royuela (2012) have shown that income inequality affects economic growth, especially when there is persistent unemployment.…”
Section: Literature Reviewmentioning
confidence: 78%
“…South Africa has been grappling with slow economic growth; high unemployment rates (the youth unemployment rate has been reported at 46.5% recently); energy crises; crime; poverty; and other economic and social ills for decades [1,2,8,9]. Mwakalila [10] posits that high unemployment rates encourage nefarious activities, social unrest, poor living conditions, and migration to other countries.…”
Section: Introductionmentioning
confidence: 99%